Evaluation of occupational exposure to static magnetic field in a chloralkali plant - AR Coobineh; F Amirzadeh (Salāmat-i kār-i Īrān, 2005)
Background and Aims: An observational cross sectional study was conducted to determine iflong term exposure to static magnetic fields could be related to findings of medical examinations.Method: Health data were obtained for 20 workers who spent a major portion of their workdaysin the magnetic fields produced by the direct current through large electrolytic cells. These datawere compared to those of a control group of 21 workers. Intensity of magnetic fields weremeasured in the cell room and the Time weighted Average (TWA) exposure to magnetic field wascalculated for each job classification.Results: Maximum and minimum intensities in mTwere found to be 16.99 and 0.46, respectively,which were well below the permissible level. Maximum TWAexposure to magnetic field wasfound to be 47.59 mTWhich were observed. Comparing the ECG, EEG, blood Pressure and pulseratesbetween the two groups showed no statistically significant differences. Clinical findingshowed that fatigue and nervousness complain were be higher in the case group and weresignificantly different between the two groups.Conclusion: We did not see statistical significant differences between case and control groups inECG, EEG, blood pressure and pulse-rates. We have seen statistically differences in the fatigue(P<0.01) and nervousness (P<0.01) complain of these two groups. We suggest that it may benecessary to choose a value of than 60 mT (TLV-TWA), so that the complains of fatigue andnervousness will be reduce.